International evidence on the relationship between Foreign Direct Investment, labour market flexibility, and economic growth - Imam, Muhammad Asim; W Azman-Saini, W. N.; Ibrahim, Saifuzzaman; W. Mohamad, Wan Norhidayah; Shafiq, Ume Salma (Human Resource Management Academic Research Society, 2024)
The study investigates the interconnected dynamics among flexible labor markets, economic growth, and foreign direct investment (F across a sample of 123 countries. Foreign direct investment has experienced steady growth and has surged significantly, emerging as a key driver of economic growth across both developing and developed countries. Utilizing the generalized method-of-moments (GMM) system model, the empirical findings highlight that a flexible labor market (FLM) significantly enhances the positive impact of FDI on economic growth. Various FDI measures are analyzed to ensure robust findings; this indicates that the marginal effect of FDI on economic growth is highly contingent upon the flexibility of the labor market. Countries with deregulated Labour markets experience greater benefits from FDI inflows. The evidence indicates that certain factors within the host country, precisely labour market policies, perform a crucial role in enhancing the growth impact of FDI.